A Project feasibility analysis on detergent from sugar and coco oil - Advincula, Ophelia; Alzona, Lynne; Bucsit, Angelina; Concio, Joselita; Ludovice, Lyna.; Trinidad, Jessica (Diliman, Quezon City College of Engineering, 1985)
Many examples indicate that the product idea is the single most important factor in business successes. As was quoted in "Project Feasibility Analysis", the golden key to success is "Get in the right business at the right time". This served as the group's guiding concept in choosing our project among several alternatives. Now, after a long and strenuous semester, we come up with this final paper which is aimed at proving the feasibility of producing a detergent bar soap out of sugar and coconut oil. In connection hereof, we hope to persuade entrepreneurs to convert this product idea into a reality in behalf of the Filipino middle to lower class consumers. The group had gone through several stages during which the various elements of this project feasibility analysis (PFA) were prepared and examined in order to reach decisions. Thus, as is required by any formal PFA, this study comprises a market analysis, a technical analysis, a financial analysis and a social profitability analysis. GENERATION AND SCREENING OF VENTURE IDEAS- Among the venture ideas the group had considered are the following: 1) detergent from sugar and coconut oil, 2) fuel from bagasse, 3) rubber from karugtong (a herbal plant), 4) fuel from inorganic wastes. Preliminary considerations were given to each one of them regarding the availability of data sources, the relevance of each on the country's present economic and social situation, the product's chance of penetrating into the local market, and other factors which the group believed to be important in any future analysis. Of them, alternative number 1 was chosen after agreeing that the product, which has been aptly named SUDS, can successfully compete with existing detergent soaps because of such an advantageous situation as the possibility of underpricing its competitive products. This cost advantage arise mainly from input materials cost, since the major raw materials are all part of the country's domestic resources. With this creation alone. the group already sensed a potential for success in pushing through with Suds' PFA. THE ANALYSES- Constraints such as competitive companies' reservation of information necessary in this study, in-availability of data sources in local research centers, and shortage of group budget to meet certain requirements in acquiring necessary data, were encountered by the group even during the early stages of analysis. But an immediate solution was provided by surveying, where our subjects were requested to indicate their weaknesses in a detergent plus other things that would be useful in our future analysis. Statistics was applied to determine the sample size required for a reliability of 95% for the household sector and 85% for the industrial sector. Most of our forecasts and generalizations were in one way or another affected by these survey results. Our data collections ranged from library searches to personal interviews to actual laboratory experiments. The group also took pains in missing some classes just to meet appointments with important persons and offices. Today, after one semester of thwarting, but nevertheless challenging, encounters with restraints, the SUDS-group (or what other people enjoy referring to as the "water-loving group" is now armed to conclude the results of its PFA, that producing detergent out of sugar and coconut oil is feasible in all aspects.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Detergents; Participatory monitoring and evaluation (Project management)